A Highly Efficient Oxygen Evolution Catalyst Consisting of Interconnected Nickel–Iron‐Layered Double Hydroxide and Carbon Nanodomains. Issue 5 (11th December 2017) - Yin, Shengming; Tu, Wenguang; Sheng, Yuan; Du, Yonghua; Kraft, Markus; Borgna, Armando; Xu, Rong
Abstract: In this work, a one‐pot solution method for direct synthesis of interconnected ultrafine amorphous NiFe‐layered double hydroxide (NiFe‐LDH) (<5 nm) and nanocarbon using the molecular precursor of metal and carbon sources is presented for the first time. During the solvothermal synthesis of NiFe‐LDH, the organic ligand decomposes and transforms to amorphous carbon with graphitic nanodomains by catalytic effect of Fe. The confined growth of both NiFe‐LDH and carbon in one single sheet results in fully integrated amorphous NiFe‐LDH/C nanohybrid, allowing the harness of the high intrinsic activity of NiFe‐LDH due to (i) amorphous and distorted LDH structure, (ii) enhanced active surface area, and (iii) strong coupling between the active phase and carbon. As such, the resultant NiFe‐LDH/C exhibits superior activity and stability. Different from postdeposition or electrostatic self‐assembly process for the formation of LDH/C composite, this method offers one new opportunity to fabricate high‐performance oxygen evolution reaction and possibly other catalysts. Abstract : A one‐pot solution method for direct synthesis of interconnected NiFe‐layered double hydroxide (NiFe‐LDH) (<5 nm) and nanocarbon using molecular precursors is presented. The confined growth of NiFe‐LDH and carbon in one single sheet results in fully integrated amorphous NiFe‐LDH/C nanohybrid with superior activity and durability for oxygen evolution reaction.